2013
DOI: 10.1080/15374416.2013.862802
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Lagged Relations Among Parenting, Children's Emotion Regulation, and Psychosocial Adjustment in Early Adolescence

Abstract: Numerous studies have reported substantive correlations between indicators of parenting, children's emotion regulation (ER), and children's psychosocial adjustment. However, studies on underlying mechanisms are scarce. Particularly in early adolescence, it is still unclear whether relations between parenting and ER are caused by adolescent behavior, by parent behavior, or by reciprocal processes. Moreover, it is unclear whether ER can be seen as an antecedent or a consequence of psychosocial adjustment. The ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 55 publications
1
44
0
1
Order By: Relevance
“…The matter of the degree to which the same construct is being measured at each age is a potential problem with cross‐lagged designs, and it is only sometimes recognized or investigated. This is a question of measurement or factor invariance . When processes and outcomes are examined prospectively across one or more developmental periods, cross‐lagged designs tend to be replaced with different measures across periods or ages .…”
Section: Resultsmentioning
confidence: 99%
“…The matter of the degree to which the same construct is being measured at each age is a potential problem with cross‐lagged designs, and it is only sometimes recognized or investigated. This is a question of measurement or factor invariance . When processes and outcomes are examined prospectively across one or more developmental periods, cross‐lagged designs tend to be replaced with different measures across periods or ages .…”
Section: Resultsmentioning
confidence: 99%
“…Whereas numerous studies exist concerning the development of coping and emotion regulation (Otterpohl & Wild, 2015;Vierhaus, Lohaus, & Ball, 2007;Zimmer-Gembeck & Skinner, 2011) and its impact on children's psychosocial functioning, only a few studies have addressed students' coping and emotion regulation strategies in classroom contexts (e.g., Davis & Levine, 2013). Based on a sample of 161 ninth graders from different German school tracks, Goetz, Frenzel, and Pekrun (2007) found that approachdor problem-focuseddstrategies are rarely reported by adolescents in the context of boredom experiences.…”
Section: Coping With and Regulation Of Achievement Emotionsmentioning
confidence: 98%
“…; Kim & Kochanska ) and even fewer in a transactional manner (Yates et al . ; Otterpohl & Wild ; Norona & Baker ).…”
Section: The Development Of Emotion Regulation Across Childhoodmentioning
confidence: 99%